Altered perceptual binding in Gilles de la Tourette syndrome. (October 2016) - Beste, Christian; Tübing, Jennifer; Seeliger, Helen; Bäumer, Tobias; Brandt, Valerie; Stock, Ann-Kathrin; Münchau, Alexander
Abstract: Gilles de la Tourette syndrome (GTS) is a common multifaceted neuropsychiatric disorder. Research in GTS has traditionally focussed on mechanisms underlying changes in motor processes in these patients. There is, however, growing interest in GTS related sensory phenomena. According to the Theory of Event-coding (TEC), sensory stimuli do not only serve representational functions but also action-related functions. In the current study, we use the TEC framework to examine whether the way perceptual features are processed is altered in GTS. The results show that basic perceptual processes differ between GTS patients and healthy controls which might be central for the understanding of this disorder. Details or features of perceptual objects were less bound in GTS suggesting that perceptual features integration is attenuated in them. Behavioural findings were unrelated to patient characteristics implying that they might represent trait abnormalities. It is possible that altered perceptual processing in GTS is due to a long-range under-connectivity of parietal areas with other brain regions repeatedly been described in these patients.